Myotoxic and cytolytic activities of dimeric Lys49 phospholipase A2 homologues are reduced, but not abolished, by a pH-induced dissociation - Angulo Ugalde, Yamileth (2005)
Lys49 phospholipase A2 (PLA2) homologues are myotoxic proteins devoid of catalytic activity. Their toxic determinants map to the C-terminal region 115–129, which plays an effector role in membrane damage. The dimeric state was reported to be essential for a Lys49 PLA2 which lost its liposome-disrupting activity after dissociating into monomers at pH 5.0. This study, evaluated the effects of a pH-induced dissociation on the toxicity of four Lys49 PLA2s, using biological targets instead. Both their cytolytic and myotoxic activities were lower at pH 5.0 than at pH 7.2. However, in contrast with experiments using artificial bilayers, toxic effects upon biological targets were not abolished at pH 5.0. Importantly, C-terminal synthetic peptides of two Lys49 PLA2s also showed lower cytolytic action at pH 5.0 than at pH 7.2, indicating that factors other than the dimeric/monomeric state of the proteins may also be involved in these differences of toxicity. Results support the view that the dimeric state of Lys49 PLA2s could play an enhancing, although not essential role, in their C-terminal region-mediated mechanism of myotoxicity.